Phytosociological parameters of a fragment of mixed ombrophilous forest in regeneration after burning in the municipality of Segredo - Silva, Maycon Thuan Saturnino da; Oliveira, Gustavo Silva; Dreyer, Jaqueline Beatriz Brixner; Schlickmann, Monique Bohora; Dreyer, Taize Caroline; Atanazio, Kemely Alves (Scientia Agraria Paranaensis, 2017)
<span style="font-family: ’Helvetica’,sans-serif; font-size: 10pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The present work aims to describe the structure and floristic composition of the natural regeneration in a clearing of a Fragment of Mixed Ombrophilous Forest that underwent an intervention by burning after three years in the Municipality of Segredo, Rio Grande do Sul State, Brazil. We sampled 16 plots of 2 x 2 m, totaling 64 m2. It was established that all plants with height greater than 0.3 m were included as criterion in the floristic survey. We found 240 plants belonging to 42 arboreal-shrub species.